EFFECT OF ZN AND ZN CONTAINING BIOACTIVE GLASSES ON EPITHELIAL MIGRATION IN AN IN-VITRO WOUND HEALING ASSAY - Uzma Khanum Mehr Ghulam; Syed Akhtar Hussain Bukhari; Muhammad Arshad Badar (Journal of University Medical & Dental College, 2016)
ABSTRACT BACKGROUND: Delayed wound healing is one of the common clinical manifestations due to moderate to severe zinc deﬁciency. This study was designed to observe effect of zinc and bioactive glasses on epithelial migration in in-vitro wound healing assays. METHODS: A simple in vitro scratch method was used in this study. Penicillin-Streptomycin solution, L-glutamine, Trypsin, Ethylenediamietetraacetic acid (EDTA), Dulbecco’s Modiﬁed Eagle’s Medium (DMEM) in glucose, phosphate buffer saline (PBS), new born or fetal calf serum (FCS), Recombinant human EGF (Invitrogen), Ethyleneglycol-bis (2-aminoethylether)-N,N,N’,N’tetraacetic acid (EGTA), zinc in the form of zinc chloride (ZnCl) and silicon as silicic acid were used for experiments. RESULTS: One pilot study and 7 experiments were conducted to observe role of Zn alone with concentrations of 10µM, 25µM, 50µM, 100µM and in combination with different concentrations of silicon. Zn (50µM) showed maximum wound closure (46.8%) however Zn (50µM) with addition of EGTA showed minimum closure of wound. The combination of Silicon and Zinc (Zn 25µM & Si 10µM) showed a wound closure of 45% and however has not shown enhanced epithelial migration as compared to controls; positive control showed 67% while negative control showed 35% of maximum closure. CONCLUSION: This study has not shown enhanced migration of HaCat cell using different treatments with Zinc and/or Silicon.